THE ROLE OF MENTORS AT TAHFIDZ ISLAMIC BOARDING SCHOOLS IN INTERNALIZING SELF-CONTROL VALUES AMONG STUDENTS IN WATAMPONE - Misbah Ahmad (Education Studies and Teaching Journal (EDUTECH), 2025)
Self-control is one of the key pillars in the continuous development of students’ character. This study aims to analyze the role of pembina (mentors) in the process of internalizing self-control values within the environment of tahfidz Islamic boarding schools in Watampone. The research employed a descriptive qualitative approach with a field research design. The study was conducted at three tahfidz pesantren: Pondok Pesantren Baytul Mukarramah, Al-Junaidiyah Biru, and Ibnu Qayyim Wahdah Islamiyah Bone. Data collection techniques included in-depth interviews, direct observation, and documentation, supported by literature review. The data were analyzed using the Miles and Huberman model, which consists of three stages: data reduction, data display, and conclusion drawing. The results of the study indicate that the role of pembina (mentors) in fostering students' self-control is carried out through four main functions: as educators, role models, motivators, and counselors. The value internalization process is implemented gradually through three stages of mentoring: ta’lim, tarbiyah, and takwin. Supporting factors include the exemplary conduct of pembina, a conducive pesantren environment, and parental involvement, while inhibiting factors include time constraints, lack of character training, and external environmental influences. The conclusion of this study highlights that pembina have a significant contribution in shaping students’ self-control cognitively, behaviorally, and morally within tahfidz Islamic boarding schools.